(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Decompressive craniectomy gives space for brain to allow outward herniation, prevents compression of brainstem structures and reconstruct brain perfusion Duroplasty further decreases ICP Objectives: The objectives of this study was to asses overall outcome of decompressive craniectomy in intracerebral hematoma (ICH), traumatic brain injury (TBI), malignant cerebral infarction and acute subdural hematoma. Methodology: This was a cross-sectional observational study conducted over patients who were undergone decompressive craniectomy subsequently from 2007 to 2014 for a period of seven (07) years. Parameter of outcome was categorized into death, favorable (Glasgow outcome scale GOS 4 or 5) and unfavorable (GOS 2 or 3). Outcome was also assessed according to preoperative GCS. The mean time of measuring outcome was 3 month. Results: The pathology for which DC done was ICH in 19 cases malignant MCA infarction in 3 cases ASH 3 cases TBI 7 cases. Decompressive craniectomy was performed in 32 cases of which 19 cases were intracerebral haematoma, 7 cases were traumatic brain injury, 3 cases were malignant cerebral infarction and 3 cases were acute subdural hematoma. Mean age was 52 years. Male female ratio was 5:3. ICH was more common in elderly age group and age range of TBI was lower than ICH. Preoperative GCS was categorized into two group 3 to 6 and 6 to 9. 14(43.25%) patients were between 3 to 6 and 18 patients 3 to 9 55(25.0%). 11(37.5%) patients died postoperatively, outcome was favorable in 12(37.5%) cases and unfavorable in 9(28.0%) cases. Outcome in relation GCS was in 3 to 6 group 3(21.0%) cases was favorable unfavorable 4(29.0%) and 7(50.0%) cases died in 6 to 9 GCS group. Outcome was favorable in 9(50.0%) cases unfavorable in 5(27.0%) cases and 4(23.0%) patients died post operatively. Conclusion: Decompressive craniectomy bears better outcome in term of survival but the problem is quality of life issue after survival especially in poor GCS (3-6) group. Journal of National Institute of Neurosciences Bangladesh, 2017;3(2): 80-83